Contamination, morphological and chemical characterization, and hazard risk analyses of microplastics in drinking water sourced from groundwater in a developing nation - Paray, Bilal Ahamad; Yu, Jimmy; Sultana, Salma; Banik, Partho; Nur, As-Ad Ujjaman; Haque, Md. Rashedul; Rahman, Md. Mostafizur; Arai, Takaomi; Yan, Li; Hossain, M. Belal (Frontiers in Environmental Science, 2024)
Groundwater (GW) plays a crucial role as the primary source of potable water in numerous developing nations. However, the increasing presence of microplastics (MPs) represents a concealed danger, threatening activities to guarantee safe drinking water in these countries. Despite this, there is limited awareness about the widespread existence of MPs in these regions of the world. In this study, we investigated the contamination levels, distribution, morphological, characteristics, chemical composition and associated public health risk of MPs in ground water samples from six coastal districts of Bangladesh using stereomicroscope and Fourier-Transform Infrared Spectroscopy (FTIR). MPs were prevalent at all sampling stations, with average concentrations of 24.63 ± 16.13 items/L and a range of 4-75 items/L. The majority of MPs (97.6%) were fibers, indicating a likely origin from fabric disintegration during drying, washing, discarded fishing nets, personal care items and municipal waste. Smaller-sized MPs (< 0.5 mm), transparent and violet-colored, were predominantly observed. Additionally, FTIR confirmed the presence of plastic polymers, including low-density polyethylene (LDPE), high-density polyethylene (HDPE), ethylene vinyl acetate (EVA) and polyethylene terephthalate (PETE). Despite the high visibility observed or focus given for PETE, PE was found to be abundant. These are thought to have come from runoff from agricultural fields, seeping from landfills where plastic trash is disposed of, synthetic fabrics, and inappropriate plastic product disposal. Estimated dietary intake was recorded as 1.85 particles/person/day (i.e., 675 particles/year), suggesting the possible health risk to the consumers.Hazard analyses based on polymeric risk score revealed diverse risks associated with polymer levels, with PETE indicating a medium risk and other polymers e.g., HDPE, LDPE, and EVA at 39%, 31%, and 17%, respectively, showing a minor risk to human health in drinking water from the studied sources. This is the first study from the regions and the findings will be valuable for identifying sources, implementing control measures, shaping policies, and safeguarding public health against plastic pollution.